دور الأجهزة المحمولة Mobile Devices فى تعزیز الحصول على المعلومات واستخدامها: دراسة استکشافیة على جامعة الامام محمد بن سعود الاسلامیة - د. على عبد المحسن على محمد (المجلة الدولية لعلوم المكتبات والمعلومات)
The purpose of this study is to identify the extent to which the communityof beneficiaries at imam university needs to obtain information using mobiledevices , the fields of information usage and the nature of their use of thesedevices. The study used the descriptive approach and relied on the questionnaireas a primary data collecting tool.The study found that the beneficiaries of the colleges of Medicine ,Computer and information , Languages and translation , Media andcommunication and Engineering are among the most popular users of mobiledevices in obtaining information. Mobile phones lead the mobile devices inobtaining information , searching for information is the first objective for thepurposes of using the Mobile devices for faculty members, as well as that imamuniversity does not provide sources of information using Mobile devices.The study recommended that the imam university library should provideappropriate applications to provide information services using mobile devices,and allocate the appropriate budgets for the development of the hardware andsoftware required to implement mobile technology in the provision of information.